Autismo infantil: perfil de pacientes atendidos em ambulatório de especialidades pediátricas em Belém, Pará. - SILVA, Sherly Cabral (2022)
BACKGROUND: Autism disorder whose etiology is not yet known, but involves genetic, immunological and environmental factors, where the child development process is profoundly distorted. It is ranked as one of the Disorders of the Global Development, characterized by losses in communication and social interaction and restricted and repetitive behavior and interests. According to latest estimates, about 1 in every 200 people has autistic spectrum disorders. OBJECTIVE: To evaluate clinical manifestations and suggest risk factors in patients who fit established diagnostic criteria for autism. METHODS: A transversal study was conducted in a non-probabilistic sample of the Children's Growth and Development Service Walk of Bettina Ferro de Souza Universitary Hospital, through information collected from 80 patients in proper research protocol, later submitted to statistical analysis. RESULTS: 77.5% of patients were male. The time of perception of events reported by most caregivers was before 3 years. Delay of language was the most frequent complaint (77.5%); 1.b 2.a were the most found criteria of DSM-IV, prevalence of seizure episodes was 32%, risperidone was the most used (77.8%) neuroleptic and Pediatric Neurology Service was the most used monitoring method. CONCLUSION: Male children were the most affected and most frequent complaint was delay in language. By DSM-IV, interaction and language are the largest losses of these patients. Seizures were associated with autistic spectrum, risperidone is the most used drug for pharmacological treatment of symptoms. It is emphasized the importance of constantly monitoring the progress of people with autistic disorder, to optimize therapeutic approach, and promote integration of new treatments and tailor articulation of multidisciplinary team.